Pandemic-Related Factors Affecting Sales in Tourism Related Businesses: A Case Study of the Nishimikawa Region, Aichi Prefecture, Japan - Mingji Cui; Hiroyuki Shibusawa (Tourism and Hospitality)
The COVID-19 pandemic severely affected Japan’s tourism-related industries, leading to significant revenue losses in the accommodation, restaurant, and tourist facility sectors. Many businesses experienced difficult situations, resulting in closures and layoffs as a result of the prolonged decline in tourism demand. Focusing on the first half of the pandemic (2020–2021), this study analyzes the loss of sales and the influencing factors among tourism-related businesses in the Nishimikawa region of Aichi Prefecture. A questionnaire survey was conducted in November 2021, and changes in sales from April 2020 to September 2021 were estimated to assess the economic impact across different sectors. A quantitative analysis was also performed to examine the relationship between sales and the state of emergency, the domestic travel subsidy program Go To Travel campaign, and business attributes. The results indicate that COVID-19 severely impacted business sales, especially in the accommodation and food service sectors, while the tourism facility and retail sectors were less affected. In the Nishimikawa region, popular for day trips from nearby areas, the Go To Travel campaign had a limited effect, highlighting the need for region-specific support measures.